Car Ownership and Private Car Use A Microeconometric Analysis Based on Norwegian Data - Dag G. Wetterwald (Statistics Norway, Research Department, 1994)
In this paper we analyze household's car ownership and private car use decisions in a model proposed by de Jong (1990). The model, which incorporates variable and fixed costs of car use, can be used to predict the effects of changes in policy measures on the car stock and aggregate use. The model is estimated on Norwegian household data for 1985.
Keywords: D12; R41; 330; Car ownership and car use; Tobit model; Heckman's two-stage procedure; misspecification.